Urban insect pests [ sustainable management strategies - Dhang, Partho (CABI, 2014)
A companion to Urban Pest Management, this book builds on the issues of insect pests in urban settings to discuss control strategies that look beyond products. From an environmental and health perspective, it is not always practical to spray chemicals idoors or in urban settings, so this work discusses sustainable control and best practice methods for managing insects that are vectors of disease, nuisance pests and the cause of structural damage.